The disappearing spoon : and other true tales of madness, love, and the history of the world from the periodic table of the elements - Kean, Sam (Little, Brown and Co., 2010)
The periodic table of the elements is a crowning scientific achievement, but it's also a treasure trove of passion, adventure, obsession, and betrayal. These tales follow carbon, neon, silicon, gold, and all the elements in the table as they play out their parts in human history. The usual suspects are here, like Marie Curie (and her radioactive journey to the discovery of polonium and radium) and William Shockley (who is credited, not exactly justly, with the discovery of the silicon transistor). Yet the more obscure characters provide some of the best stories, like Paul Emile François Lecoq de Boisbaudran, whose discovery of gallium, a metal with a low melting point, gives this book its title: a spoon made of gallium will melt in a cup of tea--From publisher description.